EFFECT OF COMPUTER ASSISTED INSTRUCTIONAL PACKAGE ON THE PERFORMANCE OF STUDENTS IN MATHEMATICS IN ILORIN METROPOLIS - Fakomogbon, Michael Ayodele; Adetayo, Omiola, Matthew; Oyebode, Awoyemi, Samson; Enuwa, Mohammed, Ridwan (European Scientific Journal, ESJ, 2014)
The purpose of this study was to determine the effect of computer assisted instructional package on the performance of students in Mathematics in Ilorin metropolis. The pretest, posttest control group design was used for the study. Eighty (80) students were randomly selected (40 males and 40 females) from two secondary schools that took part in the study. The students were randomly assigned to the experimental and control groups respectively. The subjects in the experimental group were taught using computer assisted instructional package (CAI) on quadratic equation while the control group were taught using conventional method. The treatment for the study was the CAI package used and the main instrument used was Computer Assisted Mathematics Achievement Test (CAMAT). Both the instrument and the treatment were subjected to content and face validation. A 25-item Computer Assisted Mathematics Achievement test was administered to the students as pretest and posttest. Two hypotheses were postulated and tested at 0.05 level of significance. From the analysis, the following findings were reached. (1) There was a significant difference between the achievement scores of students taught mathematics with CAI package and those taught using conventional method (t = 15.74, df = 39, p â‰¤ 0.05) (2) There was no significant difference between the mean achievement scores of male and female students taught Mathematics with CAI package (t = 0.31, df = 19, P â‰¥ 0.05). Based on these findings, it is recommended that Mathematics teachers should be encouraged to use CAI package for teaching related concepts in Mathematics.